Design Explorations for 3D-Printed Modular Markers for eXtended-Reality Tangible User Interfaces: - Iok Fong, Chau; Cardoso, Jorge C. S.; Estadieu, Gerald Vincent (International Journal of Creative Interfaces and Computer Graphics, 2022)
Various materials, objects, and sensors have been explored earlier for creating tangible user interfaces (TUIs). However, there is little work on 3D-printed TUIs based on visual markers for smartphone-based extended reality (XR) experiences. The combination of visual markers and smartphones results in cheap, accessible XR systems within reach of many people. Combined with 3D printing, it could foster do-it-yourself (DIY) projects for XR experiences, which may further expand and open-up possibilities for accessible and tangible interaction. This work explores the design space of modular 3D-printed tangibles for smartphone-based XR. The authors report the design exploration process, provide several interactive 3D-printed markers, and reflect on the resulting possibilities.